Implementation of the Principle of Legal Equality in Making Deeds of Gifts and Wills Originating from Joint Property Reviewed Based on Relevant Legislation - Karamina, Elvani; Nugroho, Bambang Daru; Kusmayanti, Hazar (Manunggal Halim Jaya, 2025)
Applying the principle of equality in law plays a vital role in protecting husbands and wives from the making of wills or deeds made without their consent. This can be examined through three main legal instruments: the Civil Code (KUH Perdata), the Compilation of Islamic Law (KHI), and Law Number 1 of 1974 concerning Marriage, as amended by Law Number 16 of 2019. This study applies a normative legal approach, namely a method that analyzes written legal norms that officially apply to the national legal system. In the context of managing joint property in marriage, the existence of consent from both parties—husband and wife—is an essential requirement that cannot be ignored. This is based on the principle that all forms of wealth obtained during the marriage bond are joint property, so they cannot be transferred, sold, donated, or used as collateral unilaterally without the consent of the spouse. Every legal action concerning joint property must be based on the agreement of both parties as a form of recognition of each party's rights to ownership. This provision aims to create justice and balance in household relationships and prevent the possibility of abuse of authority by one party. Therefore, the active involvement of the spouse in giving consent is an essential aspect to ensure the validity of a legal action and the proportional protection of rights over joint assets.